The addition of high magnifying endoscopy improves rates of high confidence optical diagnosis of colorectal polyps - Iwatate, Mineo; Sano, Yasushi; Hattori, Santa; Sano, Wataru; Hasuike, Noriaki; Ikumoto, Taro; Kotaka, Masahito; Murakami, Yoshitaka; Hewett, David G.; Soetikno, Roy; Kaltenbach, Tonya; Fujimori, Takahiro (Endoscopy International Open, 2015)
Background and study aims: The real-time optical diagnosis of colorectal polyps with high confidence predictions can achieve high levels of accuracy. Increasing the rates of high confidence optical diagnosis can improve the clinical application of real-time optical diagnosis in routine practice. The primary aim of this prospective study was to evaluate whether high magnifying endoscopy improves the rates of high confidence narrow-band imaging (NBI) – based optical diagnosis for differentiating between neoplastic and non-neoplastic colorectal lesions according to the NBI international colorectal endoscopic (NICE) classification.Patients and methods: Consecutive adult patients undergoing colonoscopy with a high magnifying (maximum, × 80) colonoscope between April and August 2012 were recruited. The optical diagnosis for each polyp was evaluated during colonoscopy in two consecutive stages by the same endoscopist, who first used NBI with non-magnifying endoscopy (NBI-NME), then NBI with magnifying endoscopy (NBI-ME). A level of confidence was assigned to each prediction.Results: The analysis included 124 patients (mean age, 56.4 years; male-to-female ratio, 72:52) with 248 polyps smaller than 10 mm. Of the 248 polyps, 210 were 1 to 5 mm in size and 38 were 6 to 9 mm in size; 77 polyps were hyperplastic, 4 were sessile serrated adenomas/polyps, 160 were low grade adenomas, 5 were high grade adenomas, and 2 were deep submucosal invasive carcinomas. The rate of high confidence optical diagnosis when NBI-ME was used was significantly higher than the rate when NBI-NME was used for diminutive (1 – 5 mm) polyps (92.9 % vs 79.5 %, P < 0.001) and for small (6 – 9 mm) polyps (94.7 % vs 84.2 %, P = 0.048).Conclusion: High magnifying endoscopy significantly improved the rates of high confidence NBI-based optical diagnosis of diminutive and small colorectal polyps.Study registration: UMIN 000007608